The impact of the development of selective attention on oral understanding to students with attention deficit disorder after cognitive rehabilitation attention function - BENCHAKHCHOUKH, Asma; DJENNANE, Amine (Journal of Human Sciences, 2020)
The current study aimed to reveal the effect of developing selective attention on the oral understanding of students with attention deficit disorder after the cognitive rehabilitation of the attention function. The study was applied to 26 pupils and seven-year-old pupils studying at the second primary level, the quasi-experimental one-group approach was used with Measurement before and after, and the study defined two stages: the first is the effectiveness of the cognitive rehabilitation plan for the function of attention, and the second is the identification of the impact of the development of selective attention on oral understanding, In the study, it was used: the behavior observation network within the section, the Attention Deficit Disorder Scale, selective attention and experiential understanding and oral, with the application of the plan re-cognitive rehabilitation of the function of attention. The results showed that there is an effect of the development of selective attention on the oral understanding of students with attention deficit disorder after the cognitive rehabilitation of the attention function, where there were statistically significant differences in the performance of the selective attention test before and after the cognitive rehabilitation of the attention function in students with attention deficit disorder. In addition to finding statistically significant differences in the oral understanding test before and after cognitive rehabilitation of the attention function of the sample members